Pengaruh Pemangkasan Pucuk dan Konsentrasi Monokalium Fosfat terhadap Produksi Benih Melon (Cucumis melo L.) Sistem Hidroponik - Moh Hasbi Ash Shidiqi; Eka Nurmala Sari; Mokhtar Effendi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of shoot pruning and the application of MKP (Monopotassium Phosphate) foliar fertilizer on melon seed production (Cucumis melo L.) in a hydroponic system. The study was conducted in Jember, East Java, using a randomized block factorial design (RAK) involving two treatment factors: shoot pruning (C1: no pruning, C2: pruning at the 20th node, C3: pruning at the 25th node) and MKP foliar fertilizer application (M1: 3 g/liter, M2: 5 g/liter), with four replicates. The parameters observed included fruit weight, number of viable seeds per fruit, fruit diameter, and weight of 1000 seeds. The results showed that pruning at the 20th node and applying a concentration of 5 g/liter of MKP (C2M2) yielded the highest results in terms of fruit weight (583,585 grams), fruit diameter (10,527 cm), and weight of 1000 seeds (18,057 grams). Meanwhile, pruning at the 20th node and applying a concentration of 3 g/liter of MKP (C2M1) produced optimal results for the parameter of number of viable seeds per fruit, which was 325,750 seeds.